2022
DOI: 10.1039/d2tb00849a
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of coinage metal-based nanomaterials to combat COVID-19 and its variants

Abstract: Multidisciplinary scientific approaches have been employed to fight against the SARS-CoV-2 pandemic and coinage metal-based nanomaterials have possessed promising antiviral ability to combat COVID-19, its variants and other contagious viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 181 publications
0
7
0
Order By: Relevance
“…Therefore, more studies have focused on functional fibers capable of inactivating pathogens. A variety of materials have been known to possess antiviral properties. This section categorizes these materials into three classes: namely, metal-based materials, carbon-based materials, and polymer-based materials. Although a number of review papers have attempted to summarize the rapid development of antiviral materials over the last 3 years, we noticed that many works have focused on medicines for in vivo activity, losing sight of the in vitro antiviral effects of recently designed textile products.…”
Section: Antiviral Textile Materialsmentioning
confidence: 99%
“…Therefore, more studies have focused on functional fibers capable of inactivating pathogens. A variety of materials have been known to possess antiviral properties. This section categorizes these materials into three classes: namely, metal-based materials, carbon-based materials, and polymer-based materials. Although a number of review papers have attempted to summarize the rapid development of antiviral materials over the last 3 years, we noticed that many works have focused on medicines for in vivo activity, losing sight of the in vitro antiviral effects of recently designed textile products.…”
Section: Antiviral Textile Materialsmentioning
confidence: 99%
“…20 There are several metal-based strategies for the fight against COVID-19, and its Omicron variants have been explored in the literature. [21][22][23][24][25] The nature of the Ni⋯Ni interaction and metalligand binding energies in nickel complexes with SARS-CoV-2 Omicron variants would be a worthwhile study. Transition metal complexes may be used as effective antivirus drugs against SARS-CoV-2 and its Omicron variants using in-silico molecular docking methods.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that some metallic and carbon-based nanomaterials like silver nanoparticles, graphene oxide, and carbon dots exhibit broad-spectrum antiviral properties. [11][12][13][14][15][16][17] Among them, graphene quantum dots (GQDs) as a kind of carbon dot (CD) have emerged as very potent antiviral nanoagents due to their low toxicity, extensive precursor sources, low cost, simple synthesis and ease of industrialization. [18][19][20][21][22] Basically, GQDs are ultra-small pieces of graphene consisting of one or a few layers (no more than 10) of graphene, and they share many properties with carbon quantum dots and graphene.…”
Section: Introductionmentioning
confidence: 99%